Catalytic Transformation of Fructose and Sucrose to HMF with Proline-Derived Ionic Liquids under Mild Conditions - Hu Li; Song Yang (International Journal of Chemical Engineering)
L-Proline derived ionic liquids (ILs) used as both solvent and catalyst were efficient for transformation of fructose and sucrose to 5-hydroxymethylfurfural (HMF) in the presence of water. Response surface methodology (RSM) was employed to optimize fructose dehydration process, and a maximum HMF yield of 73.6% could be obtained at 90°C after 50 min. The recycling of the IL exhibited an almost constant activity during five successive trials, and a possible reaction mechanism for the dehydration of fructose to HMF was proposed.